EGFR inhibitor-induced cut-like skin lesions of the fingers. (1st August 2018) - Iskandar, Andrew S; Hwang, Andrew; Dasanu, Constantin A
Abstract : Cetuximab and osimertinib are epidermal growth factor receptors (EGFRs) inhibitors used in the treatment of several malignancies. These agents have been associated with several skin lesions, the most common being papulopustular acneiform rash involving the face, neck, chest and back. Herein, we describe a unique toxic effect of these agents involving the fingertips and lateral aspects of fingers in a small patient series. The lesions presented approximately 4 weeks into treatment were cut-like and caused local discomfort/pain. Application of a colloidal solution allowed for partial resolution of these lesions in one patient, while discontinuation of the drug led to the disappearance of the lesions in another. Thus, we call for awareness of this unique skin toxicity with the use of EGFR inhibitors in patients with cancer.